2014
DOI: 10.1080/10255842.2014.946913
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: a multi-dimensional description of knee laxity using radial basis functions

Abstract: The net laxity of the knee is a product of individual ligament structures that provide constraint for multiple degrees of freedom (DOF). Clinical laxity assessments are commonly performed along a single axis of motion, and lack analyses of primary and coupled motions in terms of translations and rotations of the knee. Radial basis functions (RBFs) allow multiple DOF to be incorporated into a single method that accounts for all DOF equally. To evaluate this method, tibiofemoral kinematics were experimentally co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Experimental knee laxity motion and loading information were processed for all DOF using the radial basis function (RBF) technique described by Cyr and Maletsky [17]. While loads were manually applied in a single plane, knees experience an inherent multiplanar response due to articular geometry constraints and the coupled constraint of passive structures pulling in different DOF.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental knee laxity motion and loading information were processed for all DOF using the radial basis function (RBF) technique described by Cyr and Maletsky [17]. While loads were manually applied in a single plane, knees experience an inherent multiplanar response due to articular geometry constraints and the coupled constraint of passive structures pulling in different DOF.…”
Section: Methodsmentioning
confidence: 99%
“…The overall knee size, tibiofemoral alignment, the ratio of medial‐to‐lateral epicondylar radii, and the articular surface's size and shape were some of the factors contributing to population variability. Studies have also shown variability in the passive range of motion between subjects 16,21–23 . For example, varus−valgus (VV) and internal−external (IE) rotation range of motion can vary between 5° and 15° and 20−45°, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown variability in the passive range of motion between subjects. 16,[21][22][23] For example, varus−valgus (VV) and internal−external (IE) rotation range of motion can vary between 5°a nd 15°and 20−45°, respectively. Larger inter-subject variability was observed in the low-stiffness region compared to the high-stiffness region.…”
Section: Introductionmentioning
confidence: 99%